2022
DOI: 10.31937/akuntansi.v14i1.2635
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Good University Governance Dan Sistem Pengendalian Internal Terhadap Kinerja Perguruan Tinggi Muhammadiyah Di Indonesia

Abstract: Abstract— This study focuses on the effect of good university governance and internal control systems on higher education performance. This research is a quantitative research using path analysis. The population in this study were all Muhammadiyah higher education in Indonesia. And as for the research sample, the entire population consists of 154 universities throughout Indonesia. The results of this study are good university governance has a positive and significant influence on the performance of Muhammadiya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…Muhammadiyah Higher Education is expected to be the initiator of transparency and accountability in every university to create public trust. Public trust is concerned with the creation of processes and governance that ensure that public resources are used appropriately (Good University Governance) (Aprilia, 2022). Surayani explained in a book entitled "Good University Governance" quoted by Muhsin concluded that one of the efforts to improve the quality of education can be done by implementing good governance in universities (Muhsin et al, 2020).…”
Section: Results and Discussion Fostering Integrity: Unveiling The Im...mentioning
confidence: 99%
“…Muhammadiyah Higher Education is expected to be the initiator of transparency and accountability in every university to create public trust. Public trust is concerned with the creation of processes and governance that ensure that public resources are used appropriately (Good University Governance) (Aprilia, 2022). Surayani explained in a book entitled "Good University Governance" quoted by Muhsin concluded that one of the efforts to improve the quality of education can be done by implementing good governance in universities (Muhsin et al, 2020).…”
Section: Results and Discussion Fostering Integrity: Unveiling The Im...mentioning
confidence: 99%